Invasive Fusarium rhinosinusitis in COVID-19 patients: report of three cases with successful management - Erami, Mahzad; Aboutalebian, Shima; Hashemi Hezaveh, Seyed Jamal; Matini, Amir Hassan; Momen-Heravi, Mansooreh; Ahsaniarani, Amir Hossein; Arani, Shirin Shafaee; Ganjizadeh, Mohsen; Mirhendi, Hossein (Frontiers in Cellular and Infection Microbiology, 2023)
Invasive fungal rhinosinusitis (IFRS) is a life-threatening infection that can occur in immunocompromised patients, including those with COVID-19. Although Mucorales and Aspergillus species are the most common causes of IFRS, infections caused by other fungi such as Fusarium are rare. In this report, we present three cases of proven rhinosinusitis fusariosis that occurred during or after COVID-19 infection. The diagnosis was confirmed through microscopy, pathology, and culture, and species identification of the isolates was performed by DNA sequencing the entire ITS1-5.8 rRNA-ITS2 region and translation elongation factor 1-alpha (TEF-1α). Antifungal susceptibility testing was conducted according to CLSI guidelines. The causative agents were identified as Fusarium proliferatum, F. oxysporum + Aspergillus flavus, and F. solani/falciforme. Treatment involved the administration of antifungal medication and endoscopic sinus surgery to remove the affected mucosa, leading to the successful resolution of the infections. However, one patient experienced a recurrence of IFRS caused by A. flavus 15 months later. Early diagnosis and timely medical and surgical treatment are crucial in reducing mortality rates associated with invasive fusariosis. Additionally, the cautious use of corticosteroids in COVID-19 patients is highly recommended.